Recreational cannabis legalization and transitions in cannabis use: findings from a nationally representative longitudinal cohort in the United States - Gunadi, Christian; Zhu, Bin; Shi, Yuyan (Addiction (Abingdon, England), 2022)
Aims This study estimated the likelihoods of individuals transitioning to different cannabis use status following recreational cannabis legalization (RCL) in the United States. Design Secondary analysis of a nationally representative longitudinal cohort in the United States. We used propensity score matching to balance individual characteristics between RCL and comparison states and generalized mixed regressions to estimate behavioral transitions in matched samples. Participants A longitudinal cohort of 21 863 individuals (6925 youths and 14 938 adults) participating in the Population Assessment of Tobacco and Health waves 3 and 4. Setting Four RCL states that implemented RCL between waves 3 and 4 (California, Massachusetts, Nevada and Maine) and comparison states in the United States. Measurements Transitions in cannabis use over the two waves: (1) from non‐users to users; (2) from non‐users to weekly users; (3) from users to non‐users. Individuals in RCL states were compared with matched individuals in (1) states with medical cannabis legalization (MCL), (2) states not legalizing cannabis (non‐legalizing) and (3) MCL and non‐legalizing states combined. Findings Among youths, the association between RCL and greater odds of transition from non‐users to users was seen in comparison with non‐legalizing states [odds ratio (OR) = 2.18, 95% confidence interval (CI) = 1.37–3.45] and combined states (OR = 1.73, 95% CI = 1.23–2.42). Evidence was lacking regarding the associations between RCL and transitions from non‐users to weekly users and from users to non‐users. Among adults, RCL was associated with greater odds of transitions from non‐users to users and non‐users to weekly users if RCL states were compared with non‐legalizing states (OR = 1.68, 95% CI = 1.15–2.46; OR = 1.82, 95% CI = 1.00–3.31, respectively) or combined states (OR = 1.51, 95% CI = 1.11–2.07; OR = 2.09, 95% CI = 1.19–3.66, respectively). RCL was also associated with lower odds of transition from users to non‐users if RCL states were compared with non‐legalizing states (OR = 0.54, 95% CI = 0.35–0.81). Conclusions There appears to be some evidence that recreational cannabis legalization in the United States is associated with elevated odds of transition to cannabis use among both youths and adults.